Proteomic characterization and comparison of the infective and adult life stage secretomes from Necator americanus and Ancylostoma ceylanicum. - Yide Wong; Bruce A Rosa; Luke Becker; Mali Camberis; Graham LeGros; Bin Zhan; Maria Elena Bottazzi; Ricardo T Fujiwara; Edita Ritmejeryte; Thewarach Laha; Sujittra Chaiyadet; Piyanan Taweethavonsawat; et al. (PLoS Neglected Tropical Diseases)
More than 470 million people globally are infected with the hookworms Ancylostoma ceylanicum and Necator americanus, resulting in an annual loss of 2.1 to 4 million disability-adjusted-life-years. Current infection management approaches are limited by modest drug efficacy, the costs associated with frequent mass drug administration campaigns, and the risk of reinfection and burgeoning drug resistance. Subunit vaccines based on proteins excreted and secreted (ES) by hookworms that reduce worm numbers and associated disease burden are a promising management strategy to overcome these limitations. However, studies on the ES proteomes of hookworms have mainly described proteins from the adult life stage which may preclude the opportunity to target the infective larva. Here, we employed high resolution mass spectrometry to identify 103 and 57 ES proteins from the infective third larvae stage (L3) as well as 106 and 512 ES proteins from the adult N. americanus and A. ceylanicum respectively. Comparisons between these developmental stages identified 91 and 41 proteins uniquely expressed in the L3 ES products of N. americanus and A. ceylanicum, respectively. We characterized these proteins based on functional annotation, KEGG pathway analysis, InterProScan signature and gene ontology. We also performed reciprocal BLAST analysis to identify orthologs across species for both the L3 and adult stages and identified five orthologous proteins in both life stages and 15 proteins that could be detected only in the L3 stage of both species. Last, we performed a three-way reciprocal BLAST on the L3 proteomes from both hookworm species together with a previously reported L3 proteome from the rodent hookworm Nippostrongylus brasiliensis, and identified eight L3 proteins that could be readily deployed for testing using well established rodent models. This novel characterization of L3 proteins and taxonomic conservation across hookworm species provides a raft of potential candidates for vaccine discovery for prevention of hookworm infection and disease.